Controlled synthesis of highly-branched plasmonic gold nanoparticles through peptoid engineering - Feng Yan (Nature Portfolio, 2018)
Peptoids are promising crystallization agents, as they offer the molecular recognition capabilities of proteins and peptides but with higher stability and synthetic tunability. Here, the authors show that sequence-defined peptoids can controllably template the formation and shape evolution of gold nanostructures with defined morphologies.